Benefits from the cooperation of non-governmental organizations with enterprises and durability of cooperation - Mackiewicz Hanna; Spodarczyk Edyta (Management)
The article attempts to determine the benefits that are the basis for permanent business cooperation with non-governmental organizations (NGOs). These benefits are presented on the basis of literature, analyzed case studies and from the point of view of business representatives and non-governmental organizations who shared their practical experience in this field with the authors of the article. On the one hand, enterprises and NGOs often operate in both geographic and market proximity in a microeconomic environment. Therefore, they can direct their activities to similar recipients of the micro environment. They deal with the same local community and its problems as well as with decisions of local self-governments. Both types of organizations are also affected by similar macroeconomic conditions supporting or limiting intersectoral cooperation.